Postural body: a systematic review about assessment methods - Petermann, Xavele Braatz; Meereis, Estele Caroline Welter (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: There are different methods for assessing body posture used in physiotherapeutic research, however, there is still no consensus on what would be the most widely used. Objective: Review the methods for body postural assessment used in research today. Method: A literature review was performed on Brazilian papers published from 2010 to 2014. This papers were found Virtual Health Library database, with Health Sciences Descriptors: posture and assessment. Results: Ten assessment methods were found, as follows: Postural Assessment Software (PAS), digital photography, photogrammetry, photography, Kendall et.al. method, Kendall et.al. method with photography, New York Postural Assessment method (NYPAM), biophotogrammetry, evaluation form, and posturograma. Among others, the most used method is PAS (15 papers), followed by Kendall et.al. method with photography (six papers). Conclusion: Various methods for body postural assessment are employed, among PAS show us that is the most used.